Representasi Nama Julukan pada Masyarakat Desa Sorkam Kanan - Chairunnisa, Luthvia; Mulyadi, Mulyadi (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
This study aims to describe the forms of nicknames in the Sorkam Kanan community and to identify the factors behind the assignment of these nicknames. This research employs a descriptive qualitative method. The primary data used in this study are directly obtained data regarding individuals with nicknames in the community. The population of this study consists of all 37 residents of Sorkam Kanan Village who have nicknames. Using a total sampling method, the sample size is 37 respondents. Data collection techniques include interviews, observation, and note-taking. Data analysis follows the interactive model of Miles and Huberman. The results show that there are thirty types of nicknames, categorized by sound imitation, characteristic attribution, abbreviation, resemblance, and place of origin. The factors influencing these nicknames are environmental, social, and familial. The most dominant category in nicknames in Sorkam Kanan Village is characteristic attribution. The purpose of assigning nicknames is to provide identification and avoid confusion. This study is expected to offer insights to the community regarding the meanings behind the nicknames in Sorkam Kanan Village.